Contributions to Modeling, Simulation and Controlling of a Pumping System Powered by a Wind Energy Conversion System - Dorin Bordeașu (MDPI AG, 2021)
At present, the energy consumption of the pumping unit represents the highest cost in operating a pumping system. Due to this reason, this paper proposes a reliable and robust solution for integrating a wind energy conversion system (WECS) into an already existing pumping system (PS), without being overly intrusive for the PS, and without altering the control strategy or the hardware of the commercial WECS. The current work begins by presenting the modeling undertaken, which includes a WECS with pitchable blades, a doubly-fed induction generator (DFIG) together with its power converter, a centrifugal pump, an induction motor (IM) with its power converter, and an irrigation network with a pressure transducer. The second part consists of the proposed three-level controller: a general controller that regulates the WECS power demand according to the pumping pressure reference; three second-level controllers; two necessary for the WECS and one for the PS; and three first level controllers, two for controlling the power converters of the WECS generator and one for controlling the pump motor power converter. Finally, the simulation results of the proposed system control strategy are presented, showing its technical feasibility and good performance.